2009
DOI: 10.1080/10428190903040014
|View full text |Cite
|
Sign up to set email alerts
|

SIL-TAL1fusion gene negative impact in T-cell acute lymphoblastic leukemia outcome

Abstract: SIL-TAL1 fusion gene and the ectopic expression of HOX11L2 are common molecular abnormalities in T-cell acute lymphoblastic leukemia (T-ALL). To verify their influence on outcome, we analyzed a Brazilian pediatric T-ALL series of cases. One hundred and ninety two children, age ranged 0-21 years old, were consecutively diagnosed and treated. Reverse transcriptase-polymerase chain reaction (RT-PCR) technique was used to identify the molecular alterations. Kaplan-Meyer method was applied to estimate overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
3
28
1
Order By: Relevance
“…Subjects were ascertained from four geographical regions assembled by a national network of acute leukaemia studies [12] and the majority of cases were included in a previous publication [6]. The exclusion criteria applied for the analysis was age (12 months) and the diagnosis of T-lymphoblastic lymphoma according to WHO classification [13,14].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subjects were ascertained from four geographical regions assembled by a national network of acute leukaemia studies [12] and the majority of cases were included in a previous publication [6]. The exclusion criteria applied for the analysis was age (12 months) and the diagnosis of T-lymphoblastic lymphoma according to WHO classification [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…After mononuclear cell separation using Ficoll-Hypaque-Hystopaque ® , immunophenotype was performed in blast cells by flow cytometry using a defined panel of monoclonal antibodies, as previously described [6] and/or by immunohistochemistry methods [13,14]. Immunological classification of T-ALL was based on criteria previously published by the European Group for the Immunological Characterization of Leukaemias [18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients exhibiting the E2A-PBX1 gene fusion, presented late relapses, after more than 3 years after the diagnosis. Different studies showed controversial results with respect to the prognosis of the patients SIL-TAL rearrangements (30)(31)(32). In the present study, early relapses after diagnosis were registered for the patients having SIL-TAL rearrangements: one patient presented relapse in less than one year from the diagnosis, the other two patients relapsed between one year and two years after the moment of diagnosis.…”
Section: Discussionmentioning
confidence: 78%